Leveraging foreign direct investment for sustainability: An approach to sustainable human development in Nigeria - Fisayo Fagbemi; Tolulope Temilola Osinubi (African Governance and Development Institute (AGDI), 2020)
The paper assesses the interconnections between FDI and human capital development in Nigeria over the period 1981-2018. The analysis is carried out with the use of both non-linear autoregressive distributed lag (NARDL) and linear ARDL bounds test approach to cointegration, and VECM Granger causality technique. Findings reveal that the effect of FDI on human capital is found to be insignificant in the long run, while it is significant in the short run. However, following the asymmetric link, the empirical evidence reveals that a rise in FDI inflows to a certain rate, in the long-run, could result in a significant increase in the level of human capital development, suggesting that the magnitude of inward FDI matters in the economy. This further implies that as FDI inflows require sound technical know-how, and more skilled labour to work with or adapt to more advanced technologies, such could draw attention to improved human capital. Results also indicate that there is unidirectional causality between FDI and human capital in the long run, which runs from human capital to FDI, suggesting that the quality of human capital matters for sustainable leverage and attractiveness of FDI inflows. By implication, it is critical to adopt policy measures that could engender the sustainable development of human capital by the government, while the underlying structural bottlenecks and protracted state of insecurity that could deter foreign investors are accorded significant attention.
Keywords: 330; Economic Development; Foreign direct investment; Human capital development; Nigeria